High-Resolution Magnetic Resonance Imaging of Aging Upper Face Fat Compartments. Issue 4 (April 2017) - Foissac, Rémi; Camuzard, Olivier; Piereschi, Sébastien; Staccini, Pascal; Andreani, Olivier; Georgiou, Charalambos; Benatar, Marc
Abstract : Background: Age-related changes in fat compartments have yet to be fully characterized. Uncertainty remains in terms of volume gains/losses or shape fluctuations over time. The authors' aim was to determine the evolution of subcutaneous fat in the aging upper face, focusing on shifts in volume and dimension. Methods: Over the course of 4.5 years, 100 faces of living female Caucasian patients were prospectively studied using high-resolution magnetic resonance imaging. Subjects were stratified by age as follows: group 1, 18 to 30 years; group 2, 30 to 60 years; and group 3, older than 60 years. Superficial temporal and central forehead compartments were delimited, analyzing respective volumes and dimensions by group. Results: In 85 patients studied, superficial temporal fat (mean volume, 5.14 cm 3 ) increased 35.48 percent in total volume between youth and old age ( p = 0.046). Overall height and magnitude of the lower one-third also increased with aging. Central forehead fat (mean volume, 2.56 cm 3 ), studied in 83 patients, showed a 209.75 percent volume gain in group 2 (versus group 1) and a 17.59 percent volume loss in group 3 (versus group 2) ( p = 0.001). Conclusion: Subcutaneous facial fat fluctuates with aging, increasing in the upper face and promoting ptosis through basal compartmental expansion.